2020
DOI: 10.3390/agronomy10040484
|View full text |Cite
|
Sign up to set email alerts
|

Container Color and Compost Substrate Affect Root Zone Temperature and Growth of “Green Giant” Arborvitae

Abstract: Container-grown nursery crops are commonly exposed to root zone stress due to inadequate moisture and supraoptimal root zone temperature (RZT). Compost substrates can improve water and nutrient retention but plant responses can vary due to physical and chemical properties. Dark color containers absorb solar radiation through the container side wall leading to excessive heat buildup in the substrate, yet white containers can reduce RZT. Compost substrates and container color were examined for effects on RZT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Such unnatural soil temperatures are routinely observed in horticultural nurseries under ‘normal’ air temperatures and, as a result, could be expected to be higher in experiments where high‐temperature stress treatments are applied. To counteract such effects, it has been recently found that using light‐coloured or white pots containing substrate mixtures maximizing soil volumetric water content could help reduce root zone temperature by up to 7–8°C (Witcher, Pickens, & Blythe, 2020a, 2020b). Deploying field‐based experimental set‐ups : conducting in situ studies where the above‐mentioned environmental drivers are closely monitored will be particularly valuable to evaluate hypotheses and outcomes obtained based on controlled‐environment approaches.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Such unnatural soil temperatures are routinely observed in horticultural nurseries under ‘normal’ air temperatures and, as a result, could be expected to be higher in experiments where high‐temperature stress treatments are applied. To counteract such effects, it has been recently found that using light‐coloured or white pots containing substrate mixtures maximizing soil volumetric water content could help reduce root zone temperature by up to 7–8°C (Witcher, Pickens, & Blythe, 2020a, 2020b). Deploying field‐based experimental set‐ups : conducting in situ studies where the above‐mentioned environmental drivers are closely monitored will be particularly valuable to evaluate hypotheses and outcomes obtained based on controlled‐environment approaches.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Such unnatural soil temperatures are routinely observed in horticultural nurseries under 'normal' air temperatures and, as a result, could be expected to be higher in experiments where high-temperature stress treatments are applied. To counteract such effects, it has been recently found that using light-coloured or white pots containing substrate mixtures maximizing soil volumetric water content could help reduce root zone temperature by up to 7-8 C (Witcher, Pickens, & Blythe, 2020a, 2020b.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Greater SDW of plants produced at the RV ecoregion may have been a consequence of lower temperatures in this ecoregion. Supraoptimal root-zone temperatures, which are common during the summer for plants produced in black containers in the middle Atlantic United States, have been shown to reduce SDW and root dry weight of woody nursery crops by more than 50% (Walden and Wright 1995;Witcher et al 2020). Although we did not record root-zone temperature in our study, air and substrate temperature are correlated positively (Gheysari et al 2010); thus, the 3.1 C higher average air temperature in the MACP ecoregion relative to the RV ecoregion suggests the root-zone temperature was also higher.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has demonstrated the protection provided to the root system in jammed plants and observations of damage to root systems after spacing unacclimated plants [9]. Additionally, white containers have also been shown to reduce max RZT and exposure time significantly compared to conventional black containers [3,17]. This research differs from previous research in that it investigates the interaction of container color and container spacing.…”
Section: Introductionmentioning
confidence: 96%
“…As the heat capacity of the substrate is higher than the surrounding air, the substrate gains heat faster than it can be lost, resulting in temperatures well over ambient. Root zone temperatures have been reported in excess of 50 • C [2,3]. The effects on root growth can easily be observed on mature plants with little root growth occurring in the south-westerly portion of the container, as it has the greatest exposure to solar radiation.…”
Section: Introductionmentioning
confidence: 99%